Same, ale nie samotne - wzory ról przyjmowanych przez żony żołnierzy zawodowych = Alone but no lonely - paterns of roles accepted by the wives of professional soldiers - Famuła-Jurczak, Anita (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of research was to reconstruct the roles of women - wives of professional soldiers and to present the areas of loneliness resulting from accepting many roles in family everyday life. The research was carried out with the technic of an interview. In the research took part the wives who have been married to soldiers for more than 20 years, and their husbands have been in Polish Army for more than 15 years. The presented results of research are a part of a wider research project which aims at reconstructing the quality of lives of women whose husbands are professional soldiers.
Keywords: kobieta; rola społeczna; rola zawodowa; samotność; grupa dyspozycyjna; woman; professional role; social roles; loneliness; available groups